The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1990
DOI: 10.1172/jci114862
|View full text |Cite
|
Sign up to set email alerts
|

Transforming growth factor-beta activity in sheep lung lymph during the development of pulmonary hypertension.

Abstract: Chronic pulmonary hypertension is associated with extensive structural remodeling of the pulmonary arterial bed. The structural changes in the arterial walls include increased production of extrace~lular matrix components and smooth muscle cell hypertrophy, changes that have been similarly induced by transforming growth factor-f, (TGF-ft) in culture. In the present study, experiments were performed to determine whether TGF-ft is present in sheep lung lymph, and whether TGF-fi levels were altered in an animal m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

1992
1992
2015
2015

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(40 citation statements)
references
References 42 publications
2
38
0
Order By: Relevance
“…The increased activation of TGF-β1 signaling in PAs was reported in idiopathic PAH patients (52) and in different PAH animal models (53,54), and inhibition of the TGF-β1 receptor activin receptorlike kinase 1 prevents the development of PAH (55). Similarly, we observed elevated TGF-β1 signaling in the PAs of hypoxia-induced PAH models.…”
Section: Ep3a/b Modulates Hypoxia-induced Mmp-2/tgf-β1 Activation By supporting
confidence: 83%
“…The increased activation of TGF-β1 signaling in PAs was reported in idiopathic PAH patients (52) and in different PAH animal models (53,54), and inhibition of the TGF-β1 receptor activin receptorlike kinase 1 prevents the development of PAH (55). Similarly, we observed elevated TGF-β1 signaling in the PAs of hypoxia-induced PAH models.…”
Section: Ep3a/b Modulates Hypoxia-induced Mmp-2/tgf-β1 Activation By supporting
confidence: 83%
“…TGF-β is one of the most potent regulators of connective tissue synthesis and controls deposition of profibrotic extracellular matrix protein. It plays a role in lung tissue remodeling following injury (39), and despite its crucial role in tissue repair, a fine bal- ance is required, as increased levels of TGF-β or its receptors have been shown to result in severe pulmonary fibrosis in rat models (40). A genetic comprehensive study has indicated that TGF-β gene modifies lung disease severity in CF (41).…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that, like other serine proteinases (32)(33)(34), EVE releases growth factors, such as basic fibroblast growth factor or transforming growth factor-,B, from the extracellular matrix and activates them. These growth factors (35,36) among others (37,38) have been implicated in pulmonary (35) and systemic vascular pathology (36 …”
Section: Discussionmentioning
confidence: 99%